Educação : dever-direito do Estado, direito-dever do cidadão; inclusão de crianças e adolescentes na escola pública - Moreira, Orlando Rochadel (2006)
The research intended to analyze the role played by the State in the development of public policies directed toward the educational inclusion. The State as spectator gave place to a State with the duty-right to take the Education to the citizen and, if it is the case, to search them in their homes. The article 208, § 3º, of the Federal Constitution decrees that "the Public Power is in charge of surveying the students for the basic education... . Considering this picture, the State and City Secretariats of Education, the State Public Prosecution Service and tens of other entities, decided to implement the Educational Census, through which all the residences of the State of Sergipe are being visited, in the search for children and adolescents excluded from the school education. This work is not carried through by sampling, but by covering 100% of the residences: 16 visited neighborhoods; 73,547 residential and not residential units were visited or 65% of the city of Aracaju; 7,554 children and adolescents were found out of school; 137 children and adolescents in need of special care and 44 without birth certificate (dec.2004). As causes for the educational exclusion, it has been pointed the lack of vacancies in the schools; the pregnancy in the adolescence; the lack of school transportation service; the unemployment of the parents; the infantile work and the incredulity in the education. All those causes are related to diverse social factors and the social-economic level is found in all the analyses.